KEPUASAN AUDITEE ATAS KUALITAS JASA AUDIT DALAM PERSPEKTIF AUDITEE (Studi Empiris pada OPD Pemerintah Provinsi Banten) - Vardjani, Nonik; Lestari, Tri; Ramdhani, Dadan (Pascasarjana Universitas Sultan Ageng Tirtayas, 2017)
This research was examine the satisfaction of auditee on quality of audit service in auditee’s perspective on OPD Banten province which is discuss the influence of competence, skepticism, the proximity between the chairman of audit team to the auditee, the proximity of the audit team members with the auditee towards satisfaction of the auditee on quality of audit services in auditee’s perspective. The object of research include PPTK and expenditure treasury used purposive sampling. The data analysis technique is multiple regression used SPSS 20.0 These results reveal that variable competence, skepticism, the proximity between the chairman of audit team with auditee, the proximity of audit team members with auditee has positive and significant impact towards satisfaction of auditee on quality of audit services at the Banten Province.Keywords: competence, skepticism, the proximity between the chairman of the audit team to the auditee, the proximity of the audit team members with the auditee, satisfaction of the auditee on quality of audit services in auditee’s perspective.